2016
DOI: 10.1111/agec.12253
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency, herd size, and exit intentions in U.S. dairy farms

Abstract: The U.S. dairy industry has seen major restructuring in recent decades. A sharp decline in the number of U.S. dairy farms and an increase in average herd sizes have accompanied exits, which have been concentrated among smaller herds. Given that more productive farms are better positioned to increase operation size and to continue operation, we hypothesize that the more technically efficient farms are better able to expand and also have stronger incentives to continue production. Using data from the USDA's 2010… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 68 publications
5
48
1
1
Order By: Relevance
“…Previous studies have noted that farm efficiency differs by region due to differences in soil quality, geographical climate, attitude and farming practices (Kompas and Che ; Dong et al . ). A recent study by Jiang and Sharp () found that the mean technical efficiency for dairy farms in the South Island (81.96 per cent) was higher than that for farms in the North Island (69.52 per cent).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have noted that farm efficiency differs by region due to differences in soil quality, geographical climate, attitude and farming practices (Kompas and Che ; Dong et al . ). A recent study by Jiang and Sharp () found that the mean technical efficiency for dairy farms in the South Island (81.96 per cent) was higher than that for farms in the North Island (69.52 per cent).…”
Section: Resultsmentioning
confidence: 97%
“…; Jiang and Sharp ; Dong et al . ) to identify a set of explanatory variables for technical inefficiency. Specifically, variables representing supplementary feed use intensification, farm size, herd size, farm location, milking frequency and shed type were selected and included in the inefficiency model.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…All the statistical tests to determine the preferred model suggest that this simple model is an inadequate representation of these data when compared with more advanced models, which is common in this literature (see, for example, Dong et al. () and Seymour (). First, including the additional labor and viticulture variables in the OLS regression improved the F ‐statistic and increased the R 2 to 0.90, as four of the nine coefficients were significantly different from zero.…”
Section: Model Selection Hypothesis Tests and Resultsmentioning
confidence: 99%
“…19.49) followed by medium (C.18.62) and large size group (C.18.01) in Karnal district. Additionally, Dong et al (2016) showed that larger size herds can continue in the production process than smaller size herds. As well, the profitability measures for larger size herds were superior to the comparable small size herds.…”
Section: Resultsmentioning
confidence: 99%